The Effectiveness of Monetary Policy in Controlling Inflation: Comparative Perspective of Emerging Markets Economies - Pertiwi, Handayani Mega (Journal of Economic Growth and Development Review, 2025)
This study analyzes the effectiveness of monetary policy in controlling inflation from a comparative perspective in seven emerging market countries during the period 2010-2023. Using panel data analysis and event study methods, this study investigates the factors that influence monetary policy transmission and its impact on price stability. Empirical results show that a 100 basis point increase in the benchmark interest rate is associated with an average decrease in the inflation rate of 0.76 percent , but with substantial variation across countries (elasticity coefficients range from -0.42 to -1.18). Central bank independence, the level of financial market development, and external vulnerability are identified as the main determinants of monetary policy effectiveness. Countries with a higher central bank independence index show better success in controlling inflation, while a high degree of economic dollarization is correlated with lower monetary policy effectiveness. This study also reveals a significant interaction between monetary and fiscal policies, where high fiscal deficits tend to reduce the effectiveness of monetary policy. These findings highlight the importance of institutional reforms, domestic financial market development, and economic policy coordination as prerequisites for effective monetary policy in emerging m countries.